Developmental impairments following severe falciparum malaria in children. - Carter, J; Ross, A; Neville, BG; Obiero, E; Katana, K; Mung'ala-Odera, V; Lees, J; Newton, C (2005)
OBJECTIVE: Neurological deficits are reported in children after cerebral malaria (CM) but little is known about the prevalence and characteristics of persisting neurocognitive consequences. The prevalence of developmental impairments following other complications of falciparum malaria, such as multiple, prolonged or focal seizures, is not known. Thus, our objective was to investigate the long-term developmental outcome of CM and malaria with complicated seizures (M/S). METHODS: We followed up a cohort of children previously exposed to CM or M/S and children unexposed to either condition. All children between 6 and 9 years of age, exposed to CM, and an equal number of children exposed to M/S were identified from databases of hospital admissions from 1991 to 1998. The unexposed group was randomly selected from a census database. The children's performance was measured using assessments of cognition, motor, speech and language, hearing and vision. A parental questionnaire was used to identify children with epilepsy. RESULTS: CM group scores were significantly lower than unexposed group scores on the assessments of higher level language (adjusted mean difference -1.63, 95% CI: -2.99 to -0.27), vocabulary (-0.02, 95% CI: -0.04 to -0.01), pragmatics (OR 2.81, 95% CI: 1.04-7.6) and non-verbal functioning (-0.33, 95% CI: -0.61 to -0.06). The areas of significantly reduced functioning for the M/S group were concentrated on phonology (OR 2.74, 95% CI: 1.26-5.95), pragmatics (OR 3.23, 95% CI: 1.2-8.71) and behaviour (OR 1.8, 95% CI: 1.0-3.23). The performance of the active epilepsy group was significantly poorer than that of the group without epilepsy on the tests of comprehension, syntax, pragmatics, word finding, memory, attention, behaviour and motor skills. CONCLUSIONS: CM and M/S are associated with developmental impairments. If these impairments persist, this may have implications for least 250,000 children in Sub-Saharan Africa each year. Active epilepsy significantly increases the risk of cognitive and behavioural problems in children with a history of severe malaria.